(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The present paper deals with the concept of intersectionality and its applications in the legal realm, with special regard to human rights law. Intersectional legal approaches have traditionally been linked to non-discrimination law, while the application in human rights law is still inconsistent, but with significant potential. The article will thus focus on the theoretical and practical developments concerning these less trodden aspects of intersectionality, to unveil in which sense it can bring innovations to legal theory and practice beyond the connection to non-discrimination. To do so, it firstly deals with the origins of the concept and subsequently focuses on its legal applications. The second part of the paper focuses on the developments of the concept of intersectionality in human rights law in general and in some specific areas thereof, i.e. climate change law, migration law, emergency law, and democratic innovations.